Perceptions of low back pain in elite gymnastics: A multi-disciplinary qualitative focus group study - Fawcett, L.; Heneghan, N. R.; James, S.; Rushton, A. (Physical Therapy in Sport, 2020)
Objectives: To explore the multidisciplinary team experience of Low Back Pain (LBP) in elite gymnastics. Design: A qualitative focus group. Setting: British Gymnastics. Participants: Ten coaching, sports science and medicine multidisciplinary team members working with British gymnasts. Main outcome measures: A topic guide informed by literature/expert opinion enabled discussion that was recorded/transcribed verbatim. Initial inductive analytic process developed theoretical insights. Manual coding using constant comparative methods categorised meaningful themes and sub-themes. Results: Two key aspects were identified. Emerging themes for LBP presentation included: early identification LBP and influence of multidisciplinary team members on outcomes; factors influencing LBP reporting e.g. coach-athlete relationship; frequent presentations of LBP and accepted norms; athlete history and physical examination e.g. training load. Emerging themes for causation of LBP included: intrinsic risk factors e.g. growth and maturation; extrinsic risk factors e.g. equipment. Conclusions: Individual responses of a gymnast to experiencing LBP were important across all themes. Some LBP was perceived as normal. The coach-athlete relationship and support team are crucial decision-makers around training load and adaptation. Early detection will help minimise time loss from training/performance to expedite healing.